Estudo da infestação de fêmeas bovinas de corte pelo Rhipichepalus (Boophilus) microplus, Haematobia irritans e Dermatobia hominis - Silva, Ana Mary da (2006)
In tropical regions, resistance of cattle to external parasites is an important factor determining efficiency of the production systems. The objectives in this study were to evaluate the degree of resistance of Nelore (NE), Canchim x Nelore (CN), Aberdeen Angus x Nelore (AN) and Simmental x Nelore (SN) females of several ages to cattle tick (Rhipicephalus (Boophilus) microplus), horn fly (Haematobia irritans) and beef-worm (Dermatobia hominis), and the possibility of selection to increase resistance of beef cattle to these parasites, through the estimation of genetic parameters of the degree of natural infestation, in order to furnish information to beef cattle breeding programs in Brazil. Two experiments were carried out. In experiment 1, 16 NE, 18 CN, 16 AN and 16 SN 16.5 months old females, were artificially infested with 20,000 larvae of cattle tick, four times 14 days apart each, were done, and from day 18 to day 22 of each infestation the number of engorged female ticks (≥ 4.5 mm) was counted on the left side of each animal. In this experiment, data were analyzed as the percentage of return (PR = percentage of ticks counted relative to the number infested), transformed to (PR)1/4, using the least squares method with a model that included effects of genetic group (GG), animal within GG (error a), infestation number (I), GG x I, and the residual (error b). In experiment 2, from six to ten cattle tick, horn fly and beef-worm countings on NE (184), CN (153), AN (123) and SN (120) naturally infested females of several physiological states (calves, pregnant and open heifers, primiparous cows with and without a calf and pluriparous cows with and without a calf), from July 2003 to December 2004, were done. In this experiment, data, transformed to log10 (n + 1), were analyzed by the least squares method with a model that included effects of genetic group (GG) of female, animal within GG (error a), year-season of counting (YS), physiological state, and GG x YS interaction. Besides that, genetic parameters of the degree of infestation by the parasites were obtained by the restricted maximum likelihood method, using models that included fixed effects of contemporary group (genetic group, year-season of counting) and physiological state, and additive direct, animal s permanent environmental, and residual random effects. In artificial infestation, despite the GG x I interaction, in general, NE animals were more resistant, followed by CN, and, at last, by SN and AN ones, which showed, respectively, the following percentage of return: 0.35 ± 0.06, 0.54 ± 0.05, 0.89 ± 0.06 and 0.85 ± 0.06. In natural infestation, the difference among genetic groups depended on year-season of counting, however, in general, NE females were less infested by ticks than females of the other genetic groups, while AN females showed higher infestation by horn flies and beef-worm than females of the other genetic groups. Heritability and repeatability estimates based on one-trait analyses were 0.12 and 0.12, 0.30 and 0.30, and 0.04 and 0.12, for infestation by cattle ticks, horn flies and beef-worms, respectively, indicating that it is feasible to obtain genetic progress for infestation by horn flies. The genetic correlations among these traits were low, except that between infestations by horn flies and beef-worms (0.60).